Analisis Pembelajaran Tematik Berbasis Kecerdasan Spiritual Siswa Sekolah Dasar - Siregar, Wardah Khoiriah; Witarsa, Ramdhan (Universitas Negeri Makassar, 2022)
This study aims to describe the thematic learning based on spiritual intelligence of elementary school students. The research method used is descriptive qualitative research method, with pre-field, field, and data analysis steps. The data sources were the fifth-grade teacher and all fifth-grade students of SDN 007 Tambusai, totaling 26 students consisting of 14 male students and 12 female students. Data collection techniques used are documentation, observation, and interviews. The research instrument used was teacher observation sheets, student observation sheets, and interview guidelines. The data analysis technique was carried out by qualitative data analysis techniques. The results showed that the thematic learning based on spiritual intelligence of elementary school students was in the very high category. The conclusion of this research is that the thematic learning based on students' spiritual intelligence is classified as very high because teachers who apply thematic learning in elementary schools have an Islamic religious education background. Teachers must be role models and must also assist students in formulating their vision and mission of life in the future.